STD vaccines–an overview. Issue 5 (October 1997) - Barbosa-Cesnik, C T; Gerbase, A; Heymann, D
Abstract : OBJECTIVES: To describe the role and current status of vaccine research against sexually transmitted diseases (STDs). METHODS: The available literature was reviewed with particular emphasis on bacterial STDs. RESULTS: Strategic approaches to possible implementation of STD vaccine programmes were analysed. The status of vaccines against bacterial STDs (syphilis, chancroid, gonorrhoea, and chlamydia) is described in detail. CONCLUSIONS: The development of safe and effective STD vaccines offers a potent tool for the control of STDs, including direct and indirect prevention of HIV infection. Future priorities should be in the development of vaccines against gonorrhoea, chlamydia, and syphilis. When such vaccines become available, caution should be exercised to ensure that they do not interfere with the effectiveness of other prevention programmes.